Policy Implementation of Pasuruan Regional Regulation No. 1 of 2015 regarding Sumber Suko, Kejayan, Pasuruan - Hambali; Rossa; Siti Ayundatus Solikha (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Policy implementation is an action carried out by individuals, officials or government or private groups directed at achieving the goals outlined in policy decisions. This research examines how policy implementation is said to be good from the perspective of A Model of the Policy Implementation according to Van Metter and Van Horn (1975). This research uses qualitative research methods. Data collection methods were carried out using observation, interviews, documentation studies, and technical triguation according to Yulianto Kadji (2014). And the data analysis techniques of Miles Huberman and Saldana (2014), namely data collection, data condensation, presenting data, drawing conclusions and verification. The results of the research show that the resources, characteristics and attitudes of implementers as well as aspects of the social and political environment have been implemented well and correctly, with standards, community resources and communication between organizations that need to be studied in more depth in their implementation in Sumber Suko Village, with supporting factors such as human and material resources. , implementing characteristics, as well as the social, economic and political environment. Meanwhile, the inhibiting factors are policy standards, community resources and time which still need to be developed and communication between organizations or agencies which is still very lacking so it needs to be developed again.